Na aquarela do Brasil: as cores se misturam na supervisão sistemática e na avaliação qualitativa no estágio acadêmico em Serviço Social - Albiero, Célia Maria Grandini (2006)
The thesis "In the Brazilian water-color: the colors are mixed with the systematic supervision and the 'Qualitative Education' in the academic internship of Social Work", illustrates the Brazilian reality regarding the professional formation in Social Work through the internship perspective under a qualitative evaluation performed during supervision. It also demonstrates through a symbolic manner, the differences between the Social Work schools located in the various regions and the local characteristics of the IES (Institutions of Superior Education). The results point to a collective direction leading to a generalizing manner, introduced by the ABEPSS (Brazilian Association of Education and Research in Social Work), and a professional project. The study aims to analyzed the evaluation process in the internship, which are unveiled within the systematic supervision of the internship. The methodology contemplates both the qualitative and quantitative aspects of the subjects through the use of virtual technology. Fourteen IES and fifty-nine subjects were the focus of the study. The analytical axis are the role of the internship, and supervision in the professional formation, as well as the qualitative evaluation in the systematic supervision of the internship. The study is presented in five distinct parts: the first part involves the internship and the systematic supervision in a qualitative perspective of the professional formation; yet, the second part demonstrates the current picture of the superior education in Brazil; in the third part the focus is on the methodology, which involves the virtual technology as a tool for the data gathering; the fourth part analyzes the research scenery and the subject of the study; finally, the fifth part attempts to unveil through the data analysis the supervision and evaluation of the internship in the Brazilian reality within the six regions that contains the ABEPSS. The qualitative evaluation in the internship assumes a participating process following a democratic and clear approach aiming the quality always based on the daily experiences, dialogue, as well as compromise. It is important to the IES to perform the internship in a systematic manner through a direct supervision allowing the supervisor to continue to target a professional growth towards a qualitative formation. The working conditions of the professor should be compatible with the requirements suggested by the pedagogic view and the student profile, as well as the proposal of the program. The study also revealed difficulties in the operational performance of the supervision. Therefore, the supervision should be systematic, constant, planned, and evaluated, based on reflections of both theoretical and practical aspects of everyday. The systematic supervision of the academic internship in the field of social work in Brazil removes the "veil" where the professional supervisor is situated - between the reality of the supervision process and the reality of its occupational space - and between 'searches' and 'escapes' from the evaluation process, which causes the professional involved as well as the social workers supervisors to aim to overcome their limits in their daily relationships and to build through a collective manner all of the possibilities of a qualitative professional practice. The docents aim to mediate the relations among them by focusing on the qualitative professional formation. Some suggestions are presented in this study to both the ABEPSS and specially the IES focused on the improvement of the professional formation in Social Work. This study has two groups of attachments, which the first one contains the tools used for the data gathering, and the other presents a CD room format containing the documents of the IES